UKCropDiversity‐HPC: A collaborative high‐performance computing resource approach for sustainable agriculture and biodiversity conservation - Lawrence Percival‐Alwyn; Ian Barnes; Matthew D. Clark; James Cockram; Michael P. Coffey; Susan Jones; Paul J. Kersey; Catherine A. Kidner; Carolin Kosiol; Bingjie Li; William A. Marsh; Ji Zhou; et al. (Plants, People, Planet)
Societal Impact Statement Diverse gene pools are fundamental to crop improvement, biodiversity maintenance and environmental management. The UKCropDiversity‐HPC high‐performance computing resource enables seven UK institutes to perform plant and conservation research with increased efficiency, cost‐effectiveness and environmental sustainability. It supports research across numerous areas, including bioinformatics, genetics, phenomics and conservation ‐ including Artificial Intelligence approaches. Its utilisation supports many United Nations Sustainable Development Goals, including Goals‐2 (Zero Hunger), −13 (Climate Action), −15 (Life on Land), −9 (Industry, Innovation and Infrastructure) and −4 (Quality Education). Accordingly, UKCropDiversity‐HPC helps maximise the societal impact of research undertaken at our seven institutes, driving positive change for future generations.